Non-uniform single-ring antenna array design using wavelet mutation based novel particle swarm optimization technique. (July 2017) - Bera, Rajesh; Mandal, Durbadal; Kar, Rajib; Ghoshal, Sakti Prasad
Abstract: Side lobe level (SLL) reduction is the key challenge in antenna array synthesis. In order to achieve low SLL in array pattern, many conventional optimization methods are proposed to handle complex, nonlinear and non-differentiable array factor of antenna array. In this article, we present an improved optimization scheme; Wavelet Mutation based Novel Particle Swarm Optimization (NPSOWM) for the synthesis of various single-ring planar arrays of isotropic antenna elements. The primary objective is to achieve the radiation pattern with minimum SLL and maximum directivity for the non-uniform, planar circular array (CA), hexagonal array (HA) and elliptical array (EA) antenna. The array pattern synthesis is done based on two parameters of the array; namely, excitation amplitude and element spacing. Two design examples are presented which illustrate the effectiveness of the NPSOWM algorithm. As compared with conventional optimization techniques like genetic algorithm (GA), simulated annealing (SA), particle swarm optimization (PSO) and its variant NPSO, NPSOWM outperforms with the goal of maximum SLL suppression.